Manajemen Inovasi Pembelajaran dalam Meningkatkan Mutu Pendidikan - Puput Puspito Rini (STAI Darul Qalam Tangerang, 2024)
Learning innovation management is a strategic domain of higher education that connects management science, pedagogy, and educational technology to design, implement, and evaluate fundamental changes to improve the quality of sustainable education.This study aims to analyze the role of learning innovation management in improving the quality of higher education through four dimensions: the integration of artificial intelligence, the evaluation of innovative models, a multi-stakeholder collaborative ecosystem, and adaptive and sustainable institutional capacity-based knowledge management.The method used is a Systematic Literature Review (SLR), designed to systematically identify, evaluate, and synthesize scientific evidence from published academic literature, prioritizing transparency, reproducibility, and scientific objectivity.The review of ten articles yielded four main categories: the integration of AI and digital technology in learning management, models and strategies for learning innovation management, the triple helix multi-stakeholder institutional collaborative ecosystem of universities, industry, and government, and knowledge management and institutional capacity development as a foundation for innovation.The study concluded that the integration of artificial intelligence improves the efficiency of evaluation and resource distribution, innovative management models boost student academic performance, triple helix collaboration builds an adaptive educational ecosystem, and knowledge management systems strengthen institutional capacity as a foundation for sustainable long-term learning innovation.